How to read world literature - Damrosch, David (Hoboken : Wiley-Blackwell, 2017)
'The study of world literature has developed at a rapid pace since the turn of the millennium. Just since this book first appeared in 2009, many new courses and several entire programs in world literature have been established, while a growing number of sophisticated studies have contributed to the expansion of world literature as a field of scholarship. These developments have also given rise to renewed debates concerning the politics of world literary study amid the ongoing stresses of globalization, including crises of migration, economic inequality, and tensions between local or national belonging and regional or religious identification. In such difficult times, it is more imperative than ever to find productive ways to read across cultures, gaining a better purchase for critical engagement both with the wider world beyond our shores and with our own home culture - or cultures. It has been a pleasure to be able to return to this book now, and I took this opportunity to expand a very succinct account into a more capacious but still accessible introduction to the key issues involved in the study of world literature today, as illustrated through a range of remarkable works from across the centuries and around the world. In preparing this new edition, which is half again the size of the first, I've brought in a range of new writers and have expanded the treatment of others. In particular, I've opened out what had been a single chapter on travel and empire into two full-length chapters'--
Machine generated contents note: Preface to the Second Edition 4 Introduction 6 1: What Is'Literature'? 17 2: Reading across Time 51 3: Reading across Cultures 91 4: Reading in Translation 129 5: Brave New Worlds 163 6: Writing Empire 203 7: Global Writing 236 Epilogue: Going Farther.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Literature -- History and criticism; Literature and globalization; LITERARY CRITICISM / General; Literature; Literature and globalization; BIOGRAPHY & AUTOBIOGRAPHY / Literary; Criticism, interpretation, etc; Electronic books